Catalyst Design for Electrochemical Reduction of CO2 to Multicarbon Products. Issue 10 (9th September 2021) - Xue, Yuanyuan; Guo, Yibo; Cui, Huijuan; Zhou, Zhen
Abstract: Electrochemical reduction of CO2 (CO2 RR), driven by renewable energy (such as wind and solar energy), is an effective route toward carbon neutralization. The multicarbon (C2+ ) products from CO2 RR are highly desirable, since they are important fuels, chemicals, and industrial raw materials. However, selective reduction of CO2 to C2+ products is especially challenging, due to low selectivity, poor yield, and high overpotential. Since the performance of CO2 RR is closely related to the structure and composition of catalysts, which alter the binding energy of intermediates generated in CO2 RR, it is necessary to study these effects systematically to achieve possible design strategies. Herein, design strategies toward catalysts for CO2 conversion to C2+ products are discussed on the basis of the adjustment of the structure and composition of catalysts, such as morphology control, defect engineering, bimetal, and surface modification. Meanwhile the reaction mechanisms and structure evolution of catalysts during CO2 RR are focused on in particular. Finally, challenges and perspectives are proposed for further improvement of CO2 RR technologies. Abstract : This review focuses on catalyst design strategies for electrochemical reduction of carbon dioxide to multicarbon products, including morphology and structure control, defect engineering, bimetal, surface modification, atomic and molecular level dispersion for Cu‐based and non‐Cu catalysts, to promote the realization of carbon neutralization.